2020
DOI: 10.1002/agj2.20327
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sitotroga cerealella infestation in wheat seeds by radiographic and multispectral images

Abstract: Radiographic and multispectral image analysis have potential to be efficient, objective methods for assessing seed quality and internal insect infestation. The aim of this study was to verify the efficiency of radiographic and multispectral analysis in detecting signs and damage caused by Angoumois grain moth [Sitotroga cerealella (Olivier)] and its different developmental stages in wheat (Triticum aestivum L.) seeds. The experiment was conducted in a completely randomized design with six replications of 50 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For MSI, seeds require very little preparation beyond the preparation required for the application or experiment at hand. For example, if the aim was to see if it is possible to identify the presence of particular fungi on seeds, the first step might be to work with sterilized seeds before inoculating them with the fungus/fungi of interest [26][27][28][29][30]. Similarly, it may be necessary to artificially age seeds for different lengths of time, to explore the use of MSI for predicting whether seeds are viable or dead, or parameters related to vigor (e.g., El Masry et al [31]).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…For MSI, seeds require very little preparation beyond the preparation required for the application or experiment at hand. For example, if the aim was to see if it is possible to identify the presence of particular fungi on seeds, the first step might be to work with sterilized seeds before inoculating them with the fungus/fungi of interest [26][27][28][29][30]. Similarly, it may be necessary to artificially age seeds for different lengths of time, to explore the use of MSI for predicting whether seeds are viable or dead, or parameters related to vigor (e.g., El Masry et al [31]).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Insect infestation has a direct effect on seed quality by consuming the seed reserves but there is also an indirect effect as it allows the establishment of secondary pests and fungi, for the storage pests lay eggs on the seed surface for the larvae to penetrate the seed coat and the larvae may undergo different larvae stages and finally produce a pupa inside the seed. X-ray and MSI have been tested for the identification of grain moth (Sitotroga cerealella) in wheat [28]. The study showed the potential of X-ray for the study of internal structures in the seed, whereas MSI showed the potential for identifying eggs on the seed surface.…”
Section: Insect Infestationmentioning
confidence: 99%
“…As it promotes an increase in temperature and humidity it favors the development of fungi and, both factors result in significant reduction of germination and seed vigor. [13][14] The introduction of the X-Ray technique represented an advance in the evaluation of seed damage, first performed on corn seeds, 15 and later expanded to soybean and sweet corn seeds. [16][17] Researches results have also revealed the efficiency of radiographic analyzes in the identification of deteriorated tissues in corn seeds, [18][19] however, the identification of these damages was only possible when the lesions are in advanced stages, making it impossible to identify them in early stages.…”
Section: Introductionmentioning
confidence: 99%